Model Transportasi Jalur Laut untuk Distribusi Semen Curah - Jenny Andres Yunirman (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2010)
Cement industry as one of economic agents in addition to technology-intensive production requires good planning also requires planning and transportation patterns of distribution of efficient and effective way to market their products. This is the focus of each cement producers, including PT. Semen Padang. Problems of distribution and transport in the PT. Semen Padang today is not having an optimal assignment system for the delivery of bulk cement sea. Distribution of bulk cement transportation model created is one form of the application of linear programming model integers. This model uses a binary 0 or 1 as a decision variable, in this case is the assignment of the ship. The objective function of this model is the minimization of transport costs to meet demand in each of the packing plant. Approach to fuzzy concepts can be applied to accommodate information that is not definite as, the number of requests in each packing plant.